Reliability and validity of the 6-item Headache Impact Test in chronic migraine from the PROMISE-2 study - Houts, Carrie R. (Qual Life Res, 2020)
PURPOSE: We examined the reliability and validity of the 6-item Headache Impact Test (HIT-6) specifically on patients with chronic migraine (CM) from the PROMISE-2 clinical trial. METHODS: The conceptual framework of HIT-6 was evaluated using baseline data from the PROMISE-2 study (NCT02974153; N = 1072). A unidimensional graded response model within the item response theory (IRT) framework was used to evaluate model fit and item characteristics. Using baseline and week 12 data, convergent and discriminant validity of the HIT-6 was evaluated by correlation coefficients. Sensitivity to change was assessed by evaluating correlations between HIT-6 scores and change scores for other established reference measures. All examined correlations were specified a priori with respect to direction and magnitude. Known-groups analyses were anchored using Patient Global Impression of Change and monthly headache days at week 12. RESULTS: A unidimensional model fit the data well, supporting that the 6 items measure a single construct. All item slopes and thresholds were within acceptable ranges. In both the validity and sensitivity to change analyses, all observed correlations conformed to directional expectations, and most conformed to magnitude expectations. Known-groups analyses demonstrated that the HIT-6 total score can distinguish between clinically meaningful CM subgroups. CONCLUSION: The HIT-6 was successfully calibrated using IRT with data from PROMISE-2. Results from these analyses were generally consistent with previous literature and provided supportive evidence that the HIT-6 is well suited for measuring the impact of headache and migraine in the CM population.